Pengaruh Klorpirifos terhadap Kadar Kreatinin Serum pada Tikus Diabetes Melitus dengan Terapi Metformin - Annisa Nurul Hamidah (Fakultas Kedokteran, 2026)
Chlorpyrifos is a broad-spectrum organophosphate pesticide widely used in agricultural activities and has been associated with systemic toxic effects, particularly involving excretory organs such as the kidneys. Continuous exposure to chlorpyrifos can increase oxidative stress, inflammatory responses, and apoptosis, potentially leading to impaired renal filtration function. Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia that triggers oxidative stress and microvascular damage, including diabetic nephropathy. Metformin is the first-line therapy for DM and is known to provide nephroprotective effects through anti-inflammatory and antioxidant mechanisms. This study aimed to assess the effect of chlorpyrifos exposure on serum creatinine levels in diabetic rats receiving metformin therapy. This experimental study was conducted at the Faculty of Medicine, University of Jember, from August to October 2025. A total of 14 male Wistar rats were randomly divided into two groups: a control group (DM + metformin 18 mg/200 gBW) and a treatment group (DM + metformin 18 mg/200 gBW + chlorpyrifos at 5 mg/kgBW/day) administered orally for 21 days. DM was induced using streptozotocin (STZ) at 40 mg/kgBW. At the end of treatment period (day 22), all rats were euthanized using ketamine-xylazine, followed by intracardiac blood sampling. Serum creatinine levels were measured using the Jaffe method and analyzed with an unpaired t-test at a significance level of p<0.05. The results showed no statistically significant difference between the control and treatment groups (p>0.05); however, there was a trend toward higher creatinine levels in the chlorpyrifos-exposed group. In conclusion, 21 days of chlorpyrifos exposure tended to increase serum creatinine levels in diabetic rats treated with metformin
Reuploud file repository 25mei 2026_Firli_Tata :: Finalisasi Repositori File 25 Mei 2026_Kurnadi
Keywords: chlorpyrifos; diabetes mellitus; metformin; creatinine; renal function